PROBLEMS OF INTEGRATION OF FORMAL AND INFORMAL EDUCATION IN CONDITIONS OF THE GENERAL INFORMATIONAL AND EDUCATIONAL ENVIRONMENT - Lyudmila P. Vladimirova (Открытое образование (Москва), 2016)
This article is devoted to the problems of integration of formal and informal education in the integrated information-educational environment. The article presents a model of integration at the level of content on the example of students learning theme «Transport». E-learning gives students opportunity both to learn together and to be independent in their study, to plan their own mode of learning.